The Role of Mirroring Behavior in the Leadership of Boarding School Administrators at Hidayatul Mubtadiin Dayamurni Islamic Boarding School - Ramandhani Nurul Hidayah; Irhamudin; Wiwied Pratiwi (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
Islamic boarding schools (pesantren), as the oldest Islamic educational institutions in Indonesia, face complex challenges in developing effective leadership among their administrators, including at Hidayatul Mubtadiin Dayamurni Islamic Boarding School. This study aims to identify the role of mirroring behavior in enhancing the effectiveness of leadership among pesantren administrators and to analyze the relationship between interpersonal mirroring and administrative performance, including its impact on discipline and character formation among students (santri). The research problem focuses on the uncertainty surrounding the relationship between two-way mirroring behavior and leadership effectiveness, as well as the risk of inconsistency that may threaten the sustainability of the administrative system. This study employs a qualitative approach using a field research model with a descriptive-analytical design. The research was conducted within the environment of Hidayatul Mubtadiin Dayamurni Islamic Boarding School, with administrators and students as the research subjects. The findings reveal that mirroring behavior manifests in three main forms: verbal mirroring (imitation of the kyai/nyai’s language style and intonation), non-verbal mirroring (imitation of body language, dress style, and gestures), and emotional synchronization (alignment of emotional states with role models). These findings confirm that administrators act as a “mirror” of authority figures, creating a cascading or tiered leadership effect that enhances students’ compliance based on respect and exemplary conduct.